Wednesday

April 23, 2014

April 23, 2014

Posted by **mazuba** on Friday, March 23, 2012 at 2:59am.

- maths -
**Reiny**, Friday, March 23, 2012 at 10:19amI think you meant

(1/8)^(12x) =2^(x+3)

(2^-3)^(12x) = 2^(x+3)

2^(-36x) = 2^(x+3)

then

-36x = x+3

-37x = 3

x = -3/37

**Related Questions**

MATHS! - Kinda lost with this one Given that hx^3 - 12x^2 - x + 3=(2x-1) (2x+1...

algebra2 - 1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators ...

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

Polynomial Fucntion Problem - Could you help me with the following problem, I ...

Algebra - Solve for y in terms of x . Determine if y is a function of x . If it ...

math, drbob222 - For this problem is it only asking for the exprssion(formula). ...

maths - f(x)=px^3 + 6x^2 + 12x + q given that the remainder when f(x) is divided...

Algebra 2 - Add(1/12X^4+6/7X^3+3/8X^2+5)+ (-7/12X^4+5/8X^2-5). "Please help me ...

algebra 2 - Add(1/12X^4+6/7X^3+3/8X^2+5)+ (-7/12X^4+5/8X^2-5). "Please help me ...

algebra 2 - Add(1/12X^4+6/7X^3+3/8X^2+5)+ (-7/12X^4+5/8X^2-5). "Please help me ...